Bibliometric Analysis of Key Findings in Studies on Gender Disparities in Education and Employment - Judijanto, Loso; Setiawati, Rahmi; Sabir, Muhammad (The Eastasouth Journal of Social Science and Humanities, 2024)
This study employs bibliometric analysis to explore the evolving landscape of research on gender disparities in education and employment from 1985 to 2024. Utilizing VOSviewer for data visualization, we identified key thematic clusters, analyzed trends over years, and pinpointed less-researched areas that present opportunities for further inquiry. Our findings revealed that while traditional topics like wage disparities and labor market participation continue to dominate the research, newer areas such as the impact of global events (e.g., COVID-19) and intersectional identities on gender inequalities are gaining prominence. Notably, the analysis highlighted significant gaps in research related to poverty, household dynamics, and health care's role in gender disparities. These findings suggest a need for a more nuanced exploration of how gender disparities affect various socioeconomic outcomes and call for targeted research efforts in underexplored areas to develop a more comprehensive understanding of the issues at hand.